Diversified legume-oilseed cropping system for synergistic enhancement of yield and water use efficiency in rainfed areas of semi-arid tropics - V. Visha Kumari; Gopinath K. A.; Sarath Chandran M. A.; A. K. Shankar; Suvana S.; Manoranjan Kumar; B. M. K. Raju; N. Jyothilakshmi; Savitha Santosh; G. Venkatesh; K. Sriram; B. Sunitha; et al. (PLoS ONE, 2025)
This study explores the development of diversified legume-oilseed cropping systems aimed at enhancing yield and water-use efficiency in rainfed areas of semi-arid tropics. Dryland agriculture, often limited by mono-cropping practices and erratic rainfall, necessitates innovative approaches for crop intensification and sustainability for the future. The integration of legumes and oilseeds into double cropping systems offers a viable solution for optimizing land use and improving productivity under precipitation-limited conditions. The research was conducted at the Gungal Research Farm of ICAR-Central Research Institute for Dryland Agriculture during the 2022-2024 cropping seasons. Six cropping systems, with and without rainwater management, were evaluated. Key findings indicate that rainwater management especially during the flowering and pod filling stage significantly enhanced crop growth, biomass accumulation, and overall yield, with safflower and sesame showing the highest adaptability to moisture stress. In terms of green gram equivalent yield, cowpea-sesame system with rainwater management achieved the highest yields, recording 1655 kg ha-1 in 2022 and 1362 kg ha-1 in 2023, highlighting the critical role of rainwater management in enhancing crop productivity in semi-arid regions. The study identified a diversified legume-oilseed cropping system as a means to achieve sustainable agricultural production in semi-arid regions.